2012
DOI: 10.1080/03235408.2011.592016
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of random amplified polymorphic DNA (RAPD) markers linked to mungbean yellow mosaic virus (MYMV) resistance in mungbean (Vigna radiata(L.) Wilczek)

Abstract: Bulk segregant analysis (BSA) and random amplified polymorphic DNA (RAPD) techniques were used to analyse the F2 individuals of susceptible VBN (Gg) 2 6 resistant KMG 189 to screen and identify the molecular marker linked to mungbean yellow mosaic virus (MYMV) resistant gene in mungbean. Two DNA bulks namely resistant bulks and susceptible bulks were setup by pooling equal amount of DNA from five randomly selected plants of each disease response. A total of 72 random sequence decamer oligonucleotide primers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 6 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…Several researchers developed the agro-infectious clones of specific virus(es) and successfully used these to screen various pulses (Table 4). To supplement further, the studies of Kartikeyan [143,144] and Bashir [145] suggested molecular markers that can be used for the indirect selection of resistant mungbean genotypes.…”
Section: Effective Phenotyping Proceduresmentioning
confidence: 99%
“…Several researchers developed the agro-infectious clones of specific virus(es) and successfully used these to screen various pulses (Table 4). To supplement further, the studies of Kartikeyan [143,144] and Bashir [145] suggested molecular markers that can be used for the indirect selection of resistant mungbean genotypes.…”
Section: Effective Phenotyping Proceduresmentioning
confidence: 99%
“…Indirect selection using DNA markers linked to resistant genes could be one of the alternate approaches as they enable marker assisted selection (MAS) to overcome the inaccuracies in the field evaluation (Selvi et al, 2006). The use of molecular markers for resistance genes is particularly powerful as it removes the delays in breeding programmes associated with the phenotypic analysis (Karthikeyan et al, 2012). This is possible due to availability of many kinds of markers viz.…”
Section: Issn: 2319-7706 Volume 7 Number 04 (2018)mentioning
confidence: 99%
“…Therefore, development and use of the virus resistant cultivars turn out to be the most effective and economical strategy against MYMV. 10 Keeping this background information into consideration, the present investigation was envisaged with the objective to identify the mungbean resistant genotypes against MYMV based on the field screening to evaluate its expediency in breeding for MYMV resistance.…”
Section: Among the Biotic Factors Mungbean Yellow Mosaic Virus (Mymv)mentioning
confidence: 99%